Konsep Kafir Perspektif Izzat Darwazah dan Implikasinya pada Realitas Kekinian - Rudy al Hana (Islamica: Jurnal Studi Keislaman, 2020)
The word kāfir is always interesting to be interpreted. Basically, this word is used by the Qur’ān to mention the unbelievers of Allah and who are hostile to Muslims in the process of Islamic da’wah. But this article will describe the use of the word kāfir in the contemporary era. Is it still relevant to be mentioned for the unbeliever of Allah? Dose it has another interpretation term in real life and evident? To answer these questions, Izzat Darwazah’s view on kāfir in the Qur’ān, i.e., al-Kāfir will be conducted as a model of interpretation. This article finds that the word kāfir, officially, cannot be removed from the Qur’ān and intellectual discourse. However, it will not be relevant to call the unbeliever as kāfir. Yet, the common word used in the democratic era is non-Muslim. This word also will eliminate the barrier between Muslim and the unbeliever in a plural society; and as linguistic analysis, more compatible than kāfir which had metaphor meaning.